Experimental investigation of inter-electrode distance and design in Cymbopogon citratus plant microbial fuel cells for sustainable energy production - Attah, N'Gissa; Kongnine, Damgou Mani; Kpelou, Pali; Mouzou, Essowè (Center of Biomass & Renewable Energy (CBIORE), 2025)
Plant Microbial Fuel Cells (PMFCs) are bioelectrochemical systems that harness plant rhizodeposition to generate electricity. This technology enables electrical energy to be produced while the plant grows. However, the major problem preventing the commercialization of these cells is their low power. In the present study, a systematic investigation was conducted to ascertain the optimal configuration of these cells, with the objective of determining the optimum inter-electrode distance. In the present stidy, the lemongrass plant (Cymbopogon citratus) was used as the main substrate source, plastic pots and graphite electrodes, while examining three single pair of electrodes configurations (PMFC-A, PMFC-B, PMFC-C), along with a unique configuration with three unaligned cathodes (PMFC-D) and three inter-electrode distances (5cm, 7.5cm and 12.5cm) were examined. The experiment focused on determining electrical parameters, plant mass growth rates and soil characteristics. These variables were measured before and after the experiment. The results indicated that the plant mass growth rate of PMFC-D exhibited the greatest magnitude (80.62%). The organic matter (OM) content in the soil exhibited an increase in each PMFC over the course of the experiment. PMFC-B exhibited the highest values of OM, electrical conductivity, and water content, respectively equal to 15.69%, 376.00µS/cm, and 15.46%. Conversely, it exhibited the lowest pH value (7.37). Electrical parameter measurements have demonstrated that PMFCs with a single pair of electrodes exhibit superior performance in comparison to those with three unaligned cathodes. Similarly, these measurements indicated that for the single pair electrode configuration, an inter-electrode distance of 7.5cm was optimal, yielding a maximum power density of 127mW/m². The determination of the average internal resistance, open circuit voltage, and power density (PD), along with their standard deviations, demonstrated that PMFC-B exhibited superior performance. Furthermore, an analysis of its autonomy revealed that the PDmin it delivers, even in the absence of sunlight, is 16.90 mW/m². From these results, PMFC-B is the best configuration for lemongrass PMFC.